2009
DOI: 10.4314/jasem.v10i2.43681
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bonny Light Crude Oil Pollution of Soil on the Growth of dayflower (Commelina benghalensis L.) in the Niger Delta, Nigeria

Abstract: ABSTRACT:The effect of Bonny Light Crude oil pollution of soil and successive plantings in the same soil at 4 -week intervals on the growth of dayflower (Commelina benghalensis L.) was investigated. The factorial sets of treatments were two levels of oil pollution (0 and 50 mg/g) and 5 successive plantings. Characters assessed were mean plant height, leaf area per plant and mean dry matter weight. At each of the 5 croppings mean plant characters assessed were significantly higher (P = 0.05) at 0 mg/g oil pollu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Brandt et al (2006) found evidence that the reduced growth and biomass found in Vetiveria zizanioides (L.) Nash (Poaceae) in the contaminated soil was related to the nutrients content. Daniel-Kalio and Pepple (2006) found that the time interval between the contamination and the establishment of seedlings affected the biomass of Commelina benghalensis L. (Commelinaceae). The same authors concluded that the time interval influenced the degradation of hydrocarbons and the availability of nutrients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brandt et al (2006) found evidence that the reduced growth and biomass found in Vetiveria zizanioides (L.) Nash (Poaceae) in the contaminated soil was related to the nutrients content. Daniel-Kalio and Pepple (2006) found that the time interval between the contamination and the establishment of seedlings affected the biomass of Commelina benghalensis L. (Commelinaceae). The same authors concluded that the time interval influenced the degradation of hydrocarbons and the availability of nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…The same substance can induce different effects in different species, and conversely, the same symptoms can arise from exposure to different substances (Baker, 1970). The most common and important symptoms observed in the plants contaminated with oil and its byproducts include the erosion of the epicuticular wax (Baker, 1970), degradation of chlorophyll (Baker, 1970;Malallah et al, 1996 and, alterations in the stomatal mechanism (Baker, 1970), reduction in photosynthesis and respiration (Baker, 1970), increase in the production of stress-related phytohormones (Larcher, 2000), accumulation of toxic substances or their byproducts in vegetal tissue (Baker, 1970), decrease in size and less production of biomass (Proffitt et al, 1995;Green et al, 1996;Kuhn et al, 1998;Brandt et al, 2006;Daniel-Kalio and Pepple, 2006;Adenipekun et al, 2008). In some cases after an oil spill, an increase in the production of biomass and in the growth and development of some species can be observed.…”
Section: Introductionmentioning
confidence: 99%
“…Crude oil affects plants in a variety of ways such as alterations in the anatomical, physiological and metabolic processes (Daniel-Kalio and Pepple, 2006;Adenipekun et al, 2008;Achuba, 2006;Achuba, 2010). Plants raised in soils tainted with petroleum have been reported to exhibit retardation in growth parameters (Onwusiri et al, 2017;Osuagwu et al, 2017) and metabolic alterations (Achuba, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Since the early seventies, there have been reported cases of crude oil spill in the Niger-Delta area with the release of more than two million barrels of crude oil into the environment (Akpovire, 1989;Daniel -Kalio and Pepple, 2006). Spilled oil has negative impact on physiological and biochemical processes in organisms resulting in major risks to the environment by poisoning exposed organisms and causing serious threats to farmland and humans (Adedokun and Ataga, 2007;DanielKalio and Pepple, 2006).…”
Section: Introductionmentioning
confidence: 99%